Impact of workplace factors on long‐term sickness absence: A retrospective observational study comparing mental and physical illnesses - Shinichi Iwasaki; Yasuhiko Deguchi; Shohei Okura; Kunio Maekubo; Ayaka Matsunaga; Koki Inoue (PCN Reports)
Abstract Aims Long‐term sickness absence (LTSA) imposes significant social and economic burdens. This study investigated how workplace factors influence the duration of LTSA for mental disorders (LTSA‐MD) and physical diseases (LTSA‐PD), hypothesizing that LTSA‐MD is more strongly associated with occupational stress than LTSA‐PD. Methods This retrospective observational study involved public servants from a Japanese municipality who had participated in the National Stress‐Check Program between 2011 and 2022. Participants were aged 20–60 years and had completed the Brief Job Stress Questionnaire (BJSQ) and subsequently availed an LTSA lasting ≥90 days. We classified sickness absence as either LTSA‐MD or LTSA‐PD using the International Classification of Diseases, Tenth Revision codes and conducted multiple linear regression analyses to evaluate the association between the BJSQ scores and LTSA duration, adjusting for sex, age, job type, and other covariates. Results The analysis included 1175 participants (LTSA‐MD 845, LTSA‐PD 330). The mean duration of LTSA‐MD was significantly longer than that of LTSA‐PD. Higher levels of supervisor support were linked to a longer LTSA‐PD duration, but there was no significant link between occupational stress and LTSA‐MD duration. Furthermore, female employees experienced longer LTSA‐MD durations than male employees, and professional workers experienced shorter durations than clerical workers. Conclusions Factors influencing LTSA duration differed between patients with mental and physical illnesses. While occupational stress did not significantly impact LTSA‐MD duration, higher supervisor support was associated with a longer LTSA‐PD duration. These findings underscore the complexity of LTSA and highlight the need for tailored interventions that address individual‐, workplace‐, and illness‐related factors.